2014
DOI: 10.2215/cjn.04160413
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Diseases

Abstract: SummaryMembranous nephropathy (MN) is an autoimmune disease usually associated with a nephrotic syndrome and it may progress to ESRD in the long term. Its etiology is often unknown (idiopathic MN), whereas other cases have a recognizable etiology (secondary MN). In idiopathic MN, the glomerular lesions are mainly caused by autoantibodies against a podocyte membrane protein, the M-type of phospholipase A2 receptor 1. The natural course of idiopathic MN is quite varied with spontaneous complete or partial remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
128
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(141 citation statements)
references
References 54 publications
3
128
0
4
Order By: Relevance
“…16 Most MN cases are iMN, representing a major cause of idiopathic NS among the adult population. 17 Despite various therapeutic strategies, the therapeutic effects are far from satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…16 Most MN cases are iMN, representing a major cause of idiopathic NS among the adult population. 17 Despite various therapeutic strategies, the therapeutic effects are far from satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Membranous nephropathy (MN), is a pathological entity characterized by diffuse thickening in the glomerular basement membrane, as viewed under light microscopy. Although 75% of MN cases are idiopathic, the remaining are associated with infections, malignancies, autoimmune diseases and drug toxicity (2).…”
Section: Introductionmentioning
confidence: 99%
“…Second, marked elevation of proteinuria associated with increased eosinophils, seen in acute phase of atheroembolism, indicated that MN disease activity of MN and the renal atheroembolism were closely related to each other. Third, in terms of pathological findings, although EDDs are likely to be exclusively subepithelial and intramembranous in idiopathic MN [6], deposits were also detected in the mesangium in this case. Negative IgG4 in parafiin section also decrease the likelihood of primary MN.…”
Section: Discussionmentioning
confidence: 63%
“…MN is most often primary, although it has been associated with hepatitis B antigenemia, autoimmune diseases, malignancies, and the use of certain drugs such as gold, penicillamine, anti-TNF-alpha therapy, and nonsteroidal anti-inflammatory drugs [6].…”
Section: Discussionmentioning
confidence: 99%